Uporaba nevromišične električne stimulacije pri težavah s požiranjem kot posledice možganske kapi, Parkinsonove bolezni in multiple skleroze z uporabo naprave Ampcare - Širca Ule, Patricija (Rehabilitacija (Ljubljana), 2021)
Background: With the development of knowledge of the physiology of swallowing and the disorders that occur in individual phases of swallowing, exercises for improving swallowing for a specific muscle group have been developed. In recent years, neuromuscular electrical stimulation (NMES) has also been used. Various devices are used abroad to perform NMES. Using the Ampcare device in combination with swallowing exercises, the possibility of improving swallowing in a patient after stroke and a patient with multiple sclerosis and associated Parkinson's disease was examined. We were interested in whether the four-week use of NMES concomitantly with speech therapy would improve swallowing. Methods: We observed the effectiveness of NMES in combination with swallowing exercises in two patients who were treated at the University Rehabilitation Institute of the Republic of Slovenia. The first patient had swallowing disorders due to stroke. The second patient had difficulty swallowing due to multiple sclerosis with associated Parkinson’s disease. A fiberoptic endoscopic evaluation of swallowing (FEES) was performed first, followed by an assessment using the MASA test and the FOIS scale. Both patients received a total of 20 cyclic stimulations lasting 30 minutes per day, five days per week (a total of four weeks). The Ampcare device was used for stimulation, and patients had to actively participate in each stimulation by performing effortful swallowing. Results: In the patient after stroke, the ability to swallow improved, he switched to complete feeding through the mouth with an adapted diet (ground and juicy food – IDDSI level 5). The patient with multiple sclerosis with associated Parkinson's disease reported an improvement in swallowing solid foods and medications, but based on speech therapist’s assessment, there was no improvement in the swallowing, the condition remained unchanged. Conclusion: The two-case study cannot be used as scientific finding, but it can serve as a basis for formulating further hypotheses in larger research. Nor can we confirm or refute research from abroad, but we can draw parallels with data on the efficacy of NMES in improving dysphagia resulting from stroke. For the field of MS and PB, the study can serve as a starting point for planning in-depth research, as it is difficult to predict solid conclusions due to the lack of such research.
Keywords: Ampcare; Deglutition Disorders; dysphagia; Electrical Stimulation; možganska kap; multipla skleroza; multiple sclerosis; neuromuscular electrical stimulation; nevrogene motnje požiranja; nevromišična električna stimulacija; Parkinson disease; Parkinsonova bolezen; rehabilitation; stroke